The MASTER (motivating, acquiring, searching, triggering, exhibiting, reflecting) learning model based on edutainment and motivation: Impact and interaction on mathematical connections skills - Suparti Suparti; Netriwati Netriwati (Journal of Advanced Sciences and Mathematics Education, 2021)
This study aimed to determine 1) the influence application of the MASTER learning model (Motivating, Acquiring, Searching, Triggering, Exhibiting, and Reflecting) based on Edutainment on students' mathematical connection skills in terms of learning motivation; 2) the influence of students' learning motivation on mathematical connection skills; and 3) the interaction between the groups of learning models (MASTER and Conventional) and the groups of learning motivation (high, moderate, and low) on students' mathematical connection skills. A quantitative research method with a quasi-experimental design was used in this study. The sample of the study was determined using cluster random sampling. The hypothesis was tested using two ways analysis of variance of unequal cells, provided that the data must be normally distributed and homogeneous. The results of the study show that 1) there was an influence of the MASTER learning model based on Edutainment on mathematical connection skills; 2) there was an influence of learning motivation on mathematical connection skills; and (3) there was no interaction between the groups of learning model (MASTER and Conventional) and the groups of learning motivation (high, moderate, and low) on mathematical connection skills.